Use of magnesit as a magnesium source for ammonium removal from leachate - Gunay, Ahmet; Karadag, Dogan; Tosun, Ismail; Ozturk, Mustafa (ELSEVIER SCIENCE BV, 2008)
Using magnesit (MgCO3) as a low cost source of magnesium ions in the struvite precipitation for the removal of high ammonium content of leachate was evaluated. Optimum molar concentration and pH conditions were analyzed to minimize the struvite solubility. Since solubility of magnesit in water is low, HCl was used to obtain soluble Mg. Maximum soluble Mg was obtained for the addition of 2 M HCl to the 1 M MgCO3 Struvite precipitation with magnesit was effective for the removal of ammonium, suspended solid, phosphate and turbidity. Economical evaluation was made comparing the costs of two magnesium sources, MgCl2 and MgCO3. The economical analysis has shown that operation cost of struvite precipitation can be reduced about 18% by using MgCO3 instead Of MgCl2. High salt concentration after struvite precipitation has no inhibitory effect on the anaerobic reactor performance. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: struvite; ammonium removal; magnesit; leachate; ANAEROBIC DIGESTER EFFLUENTS; WASTE-WATER; LANDFILL LEACHATE; PHOSPHATE; RECOVERY; PRECIPITATION; PHOSPHORUS; Engineering; Environmental Sciences & Ecology